Forgetting is a feature, not a bug: intentionally forgetting some things helps us remember others by freeing up working memory resources - Popov, Vencislav; Rummel, Jan (Psychological science, 2019)
In the present study, we used an item-method directed-forgetting paradigm to test whether instructions to forget or remember one item affect memory for subsequently studied items. In two experiments (Ns = 138 and 33, respectively), recall was higher when a word pair was preceded during study by a to-be-forgotten word pair. This effect was cumulative: Performance increased when more preceding study items were to be forgotten. The effect decreased when memory was conditioned on instructions for items appearing farther back in the study list. Experiment 2 used a dual-task paradigm that suppressed, during encoding, verbal rehearsal or attentional refreshing. Neither task removed the effect, ruling out that rehearsal or attentional borrowing is responsible for the advantage conferred from previous to-be-forgotten items. We propose that memory formation depletes a limited resource that recovers over time and that to-be-forgotten items consume fewer resources, leaving more resources available for storing subsequent items. A computational model implementing the theory provided excellent fits to the data.